Optimal Tariffs and Subsidies And Changes in Markets Structure - Dominik Egli; Frank Westermann (Center for Economic Studies and ifo Institute (CESifo), 2000)
We present a unified treatment of optimal trade policy for a small country. The well-known results for duopoly and competitive markets emerge as benchmark cases of our model. In addition, we show that changes in market structure have non-monotonic effects on optimal tariffs. Our results suggest that the recent reduction of tariffs in Eastern Europe is consistent with welfare maximizing trade policy in response to the substantial changes in the market structure of these countries.
Keywords: 330; Market structure; strategic trade policy; rent shifting